The Design of Promoting Building Energy Saver with Mobile Controller - Azliana Akmal Jamaludin, Nor; Ahmad, Arniyati; Fatimah Awang, Nor; Zainol, Zuraini (International Journal of Engineering and Technology, 2018)
Today, advance development of automation technology has totally changed our life that much easier in all aspects.Â This cause the automatic systems are more preferable over manual system. Since the increment of internet users over the past decade has made Internet as essential part of our life.Â With arising of Internet of Things (IoT) technology as expanding network that connect every object from manufacturing machine to userâ€™sÂ home appliances forÂ information sharing. This support the usage of IOT in Wireless Smart Building System to handle basic building functions automatically over internet from anywhere. Although smart building previously used to save the electric power and human energy, building with automation system differs from other system because it allows user to operate the system remotely through the internet connection. In this study, we present a design of a Smart Building System using Arduino that consist of cloud and wireless communication which allows user to control their home appliances like fans, light, air conditioner and many moreÂ in their building and storing theÂ usage data in the cloud. The building system adjusts automatically based on sensorsâ€™ data. The designed system was low cost and expandable, which accept a variety of devices to be controlled. This paper shares the architecture designs and development methodology of the system.Â Â